2020
DOI: 10.3102/1076998620911934
|View full text |Cite
|
Sign up to set email alerts
|

Variational Bayes Inference for the DINA Model

Abstract: In this article, we propose a variational Bayes (VB) inference method for the deterministic input noisy AND gate model of cognitive diagnostic assessment. The proposed method, which applies the iterative algorithm for optimization, is derived based on the optimal variational posteriors of the model parameters. The proposed VB inference enables much faster computation than the existing Markov chain Monte Carlo (MCMC) method, while still offering the benefits of a full Bayesian framework. A simulation study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…In addition, the standard errors (SEs) of estimates may sometimes be inaccurate. Yamaguchi and Okada (2020) showed that the SE estimates for correct item response probability parameters, which should range from zero to one, are sometimes larger than one in the DINA model.…”
Section: Standard Errors In Diagnostic Classification Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the standard errors (SEs) of estimates may sometimes be inaccurate. Yamaguchi and Okada (2020) showed that the SE estimates for correct item response probability parameters, which should range from zero to one, are sometimes larger than one in the DINA model.…”
Section: Standard Errors In Diagnostic Classification Modelsmentioning
confidence: 99%
“…To open the box, a complete data Fisher information matrix can be made available, and the observed Fisher information matrix can be estimated to adjust the complete data matrix (Meng & Rubin, 1991) in mixture models. In addition, DCMs are fundamentally the sub-models of general mixture models (Gu & Xu, 2019;Rupp & Templin, 2008;Yamaguchi, 2020;Yamaguchi & Okada, 2020, 2021Yamaguchi & Templin, in press). Moreover, the complete data Fisher information matrix is easier to derive than the observed data Fisher information matrix (Meng & Rubin, 1991).…”
Section: Standard Errors In Diagnostic Classification Modelsmentioning
confidence: 99%
“…Wang et al [15] used the expectation-maximization algorithm to solve the estimated values of the parameters in the Bayesian model. Yamaguchi and Okada [16] proposed a variational Bayes inference method, which applied the iterative algorithm for optimization, for the deterministic input noisy model of cognitive diagnostic assessment. Carlon et al [17] used the stochastic gradient descent and its accelerated counterpart, which employs Nesterov's method, to solve the optimization problem in optimal experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…Humphreys and Titterington (2003) and White and Murphy (2014) derived a VB inference algorithm for latent class models. Furthermore, there has been recent work which has led to the development of VB inference algorithm for DCMs (Yamaguchi, 2020;Yamaguchi & Okada, 2020. In particular, Yamaguchi and Okada (2021) introduced a mixture model formulation of the DCMs and derived a VB estimation algorithm for general DCMs that extended the algorithm initially based on the DINA model (Yamaguchi & Okada, 2020) and the multiple-choice DINA model (Yamaguchi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there has been recent work which has led to the development of VB inference algorithm for DCMs (Yamaguchi, 2020;Yamaguchi & Okada, 2020. In particular, Yamaguchi and Okada (2021) introduced a mixture model formulation of the DCMs and derived a VB estimation algorithm for general DCMs that extended the algorithm initially based on the DINA model (Yamaguchi & Okada, 2020) and the multiple-choice DINA model (Yamaguchi, 2020). Yamaguchi and Okada (2021) indicated the VB estimation method provided similar parameter estimates as MCMC estimation but at a much faster estimation time.…”
Section: Introductionmentioning
confidence: 99%